The Power of Pedagogy: Teacher Language Authority in EFL - Yulia Indah Sari Nasution; Margana (Didaktika: Jurnal Kependidikan, 2025)
Although power teacher has been widely studied, many investigations lack linguistic depth, leaving the nuanced meanings of classroom discourse underexplored. This study critically examines how teacher power is linguistically enacted and perceived in English as a Foreign Language (EFL) classroom interactions and how it shapes student learning. The research aims to (1) ident ify the types of power enacted by teachers, (2) explore students’ perceptions of these power dynamics, and (3) assess their impact on EFL learning. A qualitative case study design was employed, drawing on Fairclough’s (1989) Critical Discourse Analysis and Raven’s (2008) typology of social power. Data were gathered through classroom observations, interviews, and document analysis and analyzed using Fairclough’s three-dimensional framework: description, interpretation, and explanation. The findings reveal five types of teacher power: legitimate (institutional authority), expert (subject knowledge), referent (student admiration), reward (praise/incentives), and coercive (disciplinary control). Information power was absent, as it is typically exercised in administrative settings. Students largely accepted teacher authority, shaped by early-established classroom norms. These power enactments positively influenced student motivation, engagement, critical thinking, confidence, and behavior. This study highlights how ethically exercised teacher power contributes to respectful and effective EFL teaching. The findings illuminate the role of discourse in constructing authority and offer implications for teacher education aimed at fostering inclusive, empowering pedagogies. Although context-specific, the study encourages further exploration of power relations across diverse educational settings to advance EFL pedagogy.